Safety and Effectiveness of High-Dose Cefazolin in Patients With High Body Weight: A Retrospective Cohort Study. (28th February 2022) - Ryu, HaYoung; Mohayya, Sana; Hong, Thomas; Modi, Mansi; Yang, Jaehee; Abdul Azim, Ahmed; Bhatt, Pinki J; Brunetti, Luigi; Narayanan, Navaneeth
Abstract: Background: Cefazolin is a commonly used antibiotic for the treatment of mild to severe infections. Despite the use of higher dose of cefazolin (3 g/dose) for surgical prophylaxis in patients with obesity, there is currently a paucity of data identifying the optimal dose to treat infections in this specific patient population. Methods: This was a multicenter, retrospective cohort study of patients who received cefazolin at weight-based (up to 9 g/day) or standard doses (up to 6 g/day) for the treatment of bacteremia or skin and soft tissue infection (SSTI). Study groups were stratified by body weight and cefazolin dose received. Primary outcome was the composite of treatment-emergent adverse events (TEAEs) and secondary outcome was treatment failure rate. Results: A total of 208 patients were included for study analysis. Fifty-nine patients had body weight >120 kg. Of these, 33 received high-dose cefazolin while 26 received standard doses. The remaining 149 patients had body weight of ≤120 kg and received standard doses. The occurrence of TEAEs did not differ across the 3 groups. The study also did not find any difference between the rate of treatment failure between groups. Conclusions: High-dose cefazolin (9 g/day) for the treatment of bacteremia or SSTIs in patients with high body weight was safe and well tolerated. Larger studies are needed to further explore the benefit of high-dose cefazolin in improving clinical outcomes. Abstract : High-dose cefazolin (9 g/day) in patients with high body weight was safe and well tolerated. Larger studies are needed to evaluate if this dosing strategy improves treatment outcome in this population compared to the standard dosing regimen.